2021
DOI: 10.3390/diagnostics11040621
|View full text |Cite
|
Sign up to set email alerts
|

Chimerism Monitoring Techniques after Hematopoietic Stem Cell Transplantation: An Overview of the Last 15 Years of Innovations

Abstract: Chimerism analysis is a well-established method for monitoring the state of hematopoietic stem cell transplantation (HSCT) over time by analyzing peripheral blood or bone marrow samples of the recipient in several malignant and non-malignant hematologic diseases. From a clinical point of view, a continuous monitoring is fundamental for an effective early therapeutic intervention. This paper provides a comparative overview of the main molecular biology techniques which can be used to study chimerism after bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…Regarding SNP-qPCR methods, it has been reported that using < 10 markers results in 80%-97% informativity, suggesting the need for a larger set of markers [13,20]. Additionally, uorescence in situ hybridization with sex chromosomes is usable only for sex-mismatched donor/recipient pairs [4]. Therefore, the high informativity of premixed markers may be an advantage of the KMR kits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding SNP-qPCR methods, it has been reported that using < 10 markers results in 80%-97% informativity, suggesting the need for a larger set of markers [13,20]. Additionally, uorescence in situ hybridization with sex chromosomes is usable only for sex-mismatched donor/recipient pairs [4]. Therefore, the high informativity of premixed markers may be an advantage of the KMR kits.…”
Section: Discussionmentioning
confidence: 99%
“…Chimerism analysis assesses proportions of hematopoietic cells from the donor (donor chimerism) and recipient (recipient chimerism), and it is used as a con rmation of engraftment and as a surrogate indicator for graft rejection or relapse [4,5]. The major techniques of chimerism analysis are PCR for short tandem repeat (STR) pro les of DNA (STR-PCR), and detection of single nucleotide polymorphisms (SNPs) with real-time quantitative PCR (qPCR)-based methods (SNP-qPCR) [4][5][6][7]. Although STR-PCR is the predominant method, technical variability among laboratories is pronounced, and the detection limit for recipient chimerism is not very low, ranging from 1-10% among studies [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sampling and methylation analysis Methylation analysis of DNA obtained from peripheral blood nucleated cells was performed in 54 cases after cord blood transplantation. Among them, chimerism analysis between donors and recipients was performed by the short tandem repeat (STR) method; 50 recipients and 95% of donors were subjected to analysis 12 . Transplant information for the 50 cases is shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Human chimerism is the presence of more than one population of genetically differentiated cells in an individual. This genetic condition can be acquired through transfusion or transplantation of cells from a donor to the patient, it can also be congenital, resulting from fusion of individual dizygotic embryos or by double-embryonic embryo transfer (Tozzo et al, 2021;Johnson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%